E-Learning and the role of grammar in mastering arabic language for non-native speakers - Yousef A. Baker, El-Ebiary; Abdul Ghani, Md Din; Mohamad Abdulaziz, Mohammad Ahmed Eltigani (2020)
E-learning is the education provided on the Internet, using modern electronic technologies to reach everything related to educational materials outside the boundaries of the educational class, and the most important terms used to express and describe it are distance education, and computerized e-learning, as it is an interactive course via the Internet, Students can interact with teachers and receive their assignments at the same time. This research aims to teach grammar to non-Arabic speaking students in a functional way, in order to address the problems of difficulty applying Arabic grammar rules to different texts, and our most important goals is to teach grammar syntax that makes the learner understand the meanings of words and the overall meaning of the sentence or text, as the functional grammar is associated with knowledge of meanings and care With it and its achievement by the learner, in addition to his knowledge of how to synthesize the sentence, whether it is an actual sentence or a noun sentence, and to improve his linguistic faculties, and the research believes that one of the most important factors that helps the success of this idea is a skilled teacher with the necessary competencies and trained to apply and develop it, as we aim to make students strive to achieve Development of the linguistic outcome before, during and after the study of Arabic science, and the research will adopt the descriptive analytical approach to achieve the required, and it is expected that the students will feel the desire to learn grammar, and their mastery in applying grammatical rules and the ability to read with understanding and can perform other skills such as conversation, dialogue and the development of writing as well as One of these results is to show the importance of e-learning in the language teaching process.